CONTENT QUALITY AND CAPTION CONSISTENCY IN INSTAGRAM PROMOTION OF POLITEKNIK NEGERI LHOKSEUMAWE - Mahrani, Mahrani; Raisa Fathia; Athina Rizqa; Andini Putri; Anwar Anwar; Maulizar Maulizar; Yulianisah Yulianisah (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This study employs a qualitative approach with a descriptive analysis method, chosen to provide an in-depth understanding of the visual content quality and caption consistency on the official Instagram account of Politeknik Negeri Lhokseumawe (@humas_pnl). Data were collected through direct observation of Instagram posts published between January 2023 and January 2024, totaling 184 uploads. The observation focused on identifying patterns in the use of visuals, the presence of captions, and the alignment between text and images. In addition, content analysis was conducted to examine visual elements such as design, color, and typography, as well as textual elements including caption length, language style, message relevance, and consistency. To strengthen the findings, secondary data were gathered from relevant literature and previous studies on digital communication strategies and higher education promotion. Data were analyzed thematically by categorizing findings into visual quality, caption effectiveness, message consistency, and text–visual alignment. The results were then interpreted to provide a comprehensive overview of the effectiveness of Instagram as a promotional strategy for higher education institutions.